DAMPAK HEALTH CAPITAL TERHADAP PERTUMBUHAN EKONOMI: PEMBUKTIAN DARI NEGARA TERPILIH DI ASIA TENGGARA DENGAN PENDEKATAN MODEL AUTOREGRESSIVE DISTRIBUTED LAG (ARDL) - Kenedi Kenedi; Irwan Sukmawan (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
The purpose of this study is to analyze the long-term impacts of health capital on economic growth in Southeast Asia from 2000 – 2021. This study employed the autoregressive distributed lag (ARDL) model to estimate the long-run and short-run nexus among the variables. Furthermore, FMOLS, DOLS and CCR were used for a more robust examination of the empirical findings. The results of this study show that health capital (proxy by health expenditure per capita) has a long-run relationship with economic growth (proxy by GDP per capita) and its impact on economic growth is positive and significant, this implies that an increase in the health expenditure per capita will increase GDP per capita. In addition, the error correction term (ECT) estimation result is negative and significant (-1,395) implying disequilibrium of short-term shocks in the previous year will experience a long-term balance adjustment in the current year with average speed of 139,5% per year